A method for producing a foamed copper-manganese alloy by electrostatic spraying and a foamed copper-manganese alloy produced by the method

CN122629347BActive Publication Date: 2026-10-20CHANGDE LYRUN MATERIAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611122496.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-20
Estimated Expiration
2046-07-28

AI Technical Summary

Technical Problem

[0008]综上,当前各类制备方法分别存在涉及成分失控、孔结构缺陷、成本高、效率低、包覆不均等的短板,难以兼顾泡沫铜锰合金对保证完整三维孔道、低成本规模化生产等的多重需求

Benefits of technology

[0051]与现有技术相比,本发明的有益效果在于下列方面:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122629347B_ABST
    Figure CN122629347B_ABST
Patent Text Reader

Abstract

The application provides a method for preparing a foamed copper-manganese alloy by electrostatic spraying and a foamed copper-manganese alloy prepared by the method. The method comprises the following steps: providing a porous substrate and pretreating the same; spraying copper-manganese alloy powder on the pretreated porous substrate by electrostatic spraying; drying and setting the electrostatically sprayed porous substrate; placing the dried and set product in a protective atmosphere for heat debinding and sintering to obtain a sintered body; and cooling the sintered body. The foamed copper-manganese alloy prepared by the method of the application has high electrical conductivity, good mechanical properties and good oxidation resistance, and is suitable for scenarios such as fuel cells, water electrolysis and battery current collectors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of porous metal functional material preparation technology, specifically relating to a method for preparing foamed copper-manganese alloy by electrostatic spraying and the foamed copper-manganese alloy prepared by this method. Background Technology

[0002] Porous metallic functional materials combine the excellent electrical and thermal conductivity of metals with the advantages of high specific surface area and high porosity of porous structures, making them irreplaceable in fields such as electrochemical energy storage, high-temperature electrocatalysis, and electromagnetic shielding. Foamed copper-manganese alloys, as porous materials in the Cu-Mn solid solution system, have a face-centered cubic crystal structure and a wide range of adjustable composition. Manganese significantly enhances the copper matrix's resistance to alkali corrosion and high-temperature oxidation, making them ideal materials for solid oxide fuel cell connectors, alkaline water electrolysis oxygen evolution electrodes, and high-rate battery current collectors. However, existing preparation processes for foamed copper-manganese alloys suffer from numerous intractable technical defects.

[0003] Firstly, electrodeposition is the traditional method for preparing foamed metals, relying on the electroplating of conductive polyurethane foam. However, the standard electrode potentials of Cu and Mn differ by 1.52 V, leading to preferential reduction of copper ions and difficulty in co-deposition of manganese. This results in a manganese content in the finished foamed metal product far below the design value, indicating a severe compositional imbalance. Furthermore, electroplating suffers from a tip effect; the electric field is weak in the deep pores of the foam, resulting in significant variations in coating thickness and easy exposure of the plating deep within the pores. This leads to extremely poor product performance consistency, failing to meet the precision requirements of high-temperature electrochemical devices.

[0004] Furthermore, powder metallurgy involves mixing copper and manganese powders with a pore-forming agent, pressing the mixture into a mold, and then sintering it at high temperatures to obtain a porous preform. However, it is difficult to prepare a complete three-dimensional interconnected pore structure with a porosity of over 80%. High-porosity preforms are prone to collapse during sintering, the decomposition rate of the pore-forming agent is uncontrollable, and the pore size is disordered with poor connectivity. The large difference in melting points between copper and manganese leads to inconsistent sintering diffusion rates, which easily results in component segregation and brittle impurities, significantly reducing the electrical and mechanical properties of the material.

[0005] Furthermore, the slurry coating method requires impregnating a finished foamed copper substrate with a manganese-based slurry. However, in this method, the slurry has poor fluidity, easily clogging the foam channels and reducing the material's permeability. In addition, the subsequent solid-state diffusion alloying in the slurry coating method requires tens of hours of high-temperature holding, resulting in low production efficiency. Moreover, the drying shrinkage of the coating can generate numerous cracks, damaging the integrity of the skeleton.

[0006] While CVD and PVD vapor deposition methods can produce uniform metal coatings, they involve high equipment costs and low mass production efficiency. For complex three-dimensional through-foam structures, vapor particles are limited by diffusion and shadowing effects, making it difficult to completely encapsulate the interior of the pores. Furthermore, CVD requires the use of flammable, explosive, and highly corrosive precursors, posing significant environmental and safety hazards; PVD suffers from low target material utilization, further increasing manufacturing costs.

[0007] Existing research on spraying can only apply functional coatings to the surface of finished copper foam, which is a secondary processing technology. It cannot directly prepare copper-manganese foam alloys from polymer templates in one step, and the uniformity of spraying and powder utilization are far inferior to electrostatic spraying. Conventional electrostatic spraying is only used for coating flat or simple workpieces, and there is no complete process solution adapted to three-dimensional porous foam that can realize in-situ alloy forming.

[0008] In summary, current preparation methods suffer from drawbacks such as uncontrolled composition, pore structure defects, high cost, low efficiency, and uneven coating, making it difficult to simultaneously meet the multiple requirements of foamed copper-manganese alloys, including ensuring complete three-dimensional channels and low-cost large-scale production. Therefore, developing a new process for preparing foamed copper-manganese alloys based on electrostatic spraying is of great significance for promoting the industrial application of high-performance porous alloy materials. Summary of the Invention

[0009] Based on the technical problems described above, the purpose of this invention is to overcome the shortcomings of existing processes such as electrodeposition, powder metallurgy, slurry coating, and vapor deposition, and to provide a method for preparing foamed copper-manganese alloys through electrostatic spraying. This method relies on pre-alloyed powder to ensure uniform composition, utilizes an electrostatic field to achieve deep-pore, all-around coating of the foam, and combines a sintering process to obtain a structurally complete porous alloy. Simultaneously, this invention also provides corresponding foamed copper-manganese alloy products that possess high conductivity, good mechanical properties, and good oxidation resistance, making them suitable for applications such as fuel cells, water electrolysis, and battery current collectors, achieving low-cost, high-efficiency production.

[0010] Specifically, according to one aspect of the present invention, a method for preparing foamed copper-manganese alloy by electrostatic spraying is provided, the method comprising the following steps: (1) Provide a porous substrate and pretreat the porous substrate, the pretreat including a conductive treatment to make the surface of the porous substrate conductive; (2) Copper-manganese alloy powder is sprayed onto a pretreated porous substrate using electrostatic spraying; (3) Dry and shape the porous substrate that has been electrostatically sprayed; (4) The dried and shaped product is placed in a protective atmosphere for hot degreasing and sintering, so that the porous matrix is ​​removed and metallurgical bonding is formed between the particles of the copper-manganese alloy powder, thereby obtaining a sintered body; (5) Cool the sintered body.

[0011] According to certain preferred embodiments of the present invention, the porous matrix is ​​selected from polyurethane foam, melamine foam or carbon fiber foam.

[0012] According to certain preferred embodiments of the present invention, the pore density of the porous matrix is ​​in the range of 10-110 PPI, preferably 30-110 PPI, more preferably 80-110 PPI, and the average pore size is in the range of 100 μm-700 μm.

[0013] According to certain preferred embodiments of the present invention, the thickness of the porous matrix is ​​in the range of 1-50 mm, preferably 1-10 mm.

[0014] According to certain preferred embodiments of the present invention, the conductivity treatment is performed by electroless nickel plating, electroless copper plating, or coating with conductive carbon paste, thereby reducing the surface resistivity of the porous substrate to 10 Ω·cm. 2 -10 4 Ω / sq.

[0015] According to certain preferred embodiments of the present invention, the pretreatment further includes a surface roughening treatment performed prior to the conductivity treatment, the surface roughening treatment comprising immersing the porous substrate in an alkaline solution with a concentration of 1-5% by weight at 40-60°C for 5-60 minutes.

[0016] According to certain preferred embodiments of the present invention, the alkaline solution is an aqueous solution of sodium hydroxide.

[0017] According to certain preferred embodiments of the present invention, the pretreatment further includes a drying process performed after the conductivity treatment, the drying process comprising drying the conductivity-treated porous substrate at 60-80°C for 30-240 minutes.

[0018] According to certain preferred embodiments of the present invention, the copper-manganese alloy powder comprises, based on its total weight: 60-90% by weight of Cu; and 10-40% by weight of Mn.

[0019] According to certain preferred embodiments of the present invention, the copper-manganese alloy powder comprises, based on its total weight: 70-85% Cu by weight; 13-28% by weight of Mn; 0.15-2.5% by weight of a modified metal, wherein the modified metal is composed of Fe and Ag, and the weight ratio of Fe to Ag is in the range of 1:6 to 1:3.

[0020] According to certain preferred embodiments of the present invention, the particle size of the copper-manganese alloy powder is in the range of 5-45 μm, preferably 10-25 μm.

[0021] According to certain preferred embodiments of the present invention, the loose packing density of the copper-manganese alloy powder is 1.5-3.5 g / cm³. 3 .

[0022] According to certain preferred embodiments of the present invention, the copper-manganese alloy powder is a spherical powder or a near-spherical powder prepared by gas atomization.

[0023] According to certain preferred embodiments of the present invention, the process parameters for electrostatic spraying are as follows: Spraying voltage: -40 to -90 kV; The distance between the spray gun and the porous substrate is 150-350 mm; The feed rate of the copper-manganese alloy powder is 50-200 g / min; The rotational speed of the porous matrix is ​​5-30 rpm.

[0024] According to certain preferred embodiments of the invention, the spraying voltage is -60 to -80 kV.

[0025] According to certain preferred embodiments of the present invention, the electrostatic spraying is applied in 2-6 coats, and the porous substrate is left to stand for 2-5 minutes after each coat before the next coat is applied.

[0026] According to certain preferred embodiments of the present invention, in the electrostatic spraying, a spraying method is adopted in which a single electrostatic spray gun reciprocates and scans in conjunction with a rotating porous substrate, wherein: the porous substrate rotates at a constant speed around its own axis, and a single electrostatic spray gun is used to perform reciprocating scanning spraying along the rotation axis of the porous substrate.

[0027] According to certain preferred embodiments of the present invention, in the electrostatic spraying, a multi-gun coordinated spraying method is adopted in conjunction with a rotating porous substrate, wherein: the porous substrate rotates at a constant speed around its own axis, and 2-4 electrostatic spray guns are used to be evenly distributed circumferentially around the porous substrate, and the included angle between adjacent spray guns is 120° or 90°.

[0028] According to certain preferred embodiments of the present invention, the electrostatic spraying is carried out in a spraying chamber with a temperature of 20-35°C and a relative humidity of less than or equal to 60% RH.

[0029] According to certain preferred embodiments of the present invention, the drying and shaping includes drying at 80-120°C for 30-120 min.

[0030] According to certain preferred embodiments of the present invention, the thermal degreasing and sintering includes a thermal degreasing stage, a pre-sintering stage, and a high-temperature sintering stage, wherein: The thermal degreasing stage includes: heating to 300-450°C at a heating rate of 1-3°C / min under an inert atmosphere, and holding at that temperature for 30-90 min; The pre-sintering stage includes: heating to 700-850℃ at a heating rate of 2-5℃ / min under a hydrogen / nitrogen mixed atmosphere, and holding at that temperature for 30-60 min. The high-temperature sintering stage includes: heating to 900-1050℃ at a heating rate of 3-8℃ / min under a hydrogen / nitrogen mixed atmosphere, and holding at that temperature for 60-180 min.

[0031] According to certain preferred embodiments of the invention, the inert atmosphere is nitrogen, argon, or a mixture of nitrogen and argon.

[0032] According to certain preferred embodiments of the invention, during the thermal degreasing stage, the oxygen content in the furnace is less than or equal to 100 ppm.

[0033] According to certain preferred embodiments of the present invention, in the pre-sintering stage and the high-temperature sintering stage, the hydrogen / nitrogen mixed atmosphere is a mixture of hydrogen and nitrogen, wherein hydrogen accounts for 5-25% by volume and nitrogen accounts for 75-95% by volume.

[0034] According to certain preferred embodiments of the invention, the dew point of the hydrogen and nitrogen mixture is less than or equal to -40°C.

[0035] According to certain preferred embodiments of the present invention, the temperature of the high-temperature sintering stage is 950-1020°C.

[0036] According to certain preferred embodiments of the present invention, the hot degreasing and sintering further includes a cooling stage after the high-temperature sintering stage, the cooling stage comprising: cooling down to below 300°C at a cooling rate of ≤5°C / min.

[0037] According to certain preferred embodiments of the present invention, the method further includes a post-processing step (6) after step (5), the post-processing step (6) being selected from one or more of reduction annealing, surface modification or precision rolling.

[0038] According to certain preferred embodiments of the present invention, the reduction annealing includes annealing at 700-900°C for 1-3 h in a hydrogen atmosphere.

[0039] According to certain preferred embodiments of the present invention, the surface modification includes growing a metal oxide functional layer on the pore wall surface of the cooled product obtained in step (5) by chemical oxidation, electroplating or chemical vapor deposition.

[0040] According to certain preferred embodiments of the present invention, the metal oxide functional layer is an array of MnO2 nanosheets or a Co-Mn-O spinel layer.

[0041] According to certain preferred embodiments of the invention, the precision rolling includes multi-pass rolling, with a reduction of 5-15% per pass.

[0042] According to another aspect of the present invention, a foamed copper-manganese alloy is provided, which is prepared by the method described above.

[0043] According to certain preferred embodiments of the present invention, the foamed copper-manganese alloy has a three-dimensional interconnected pore structure, wherein the porosity is in the range of 60-90%.

[0044] According to certain preferred embodiments of the present invention, the pore walls of the foamed copper-manganese alloy comprise 60-90% by weight of Cu and 10-40% by weight of Mn.

[0045] According to certain preferred embodiments of the present invention, the pore walls of the foamed copper-manganese alloy comprise: 70-85% by weight Cu, 13-28% by weight Mn and 0.15-2.5% by weight modified metal, wherein the modified metal is composed of Fe and Ag, wherein the weight ratio of Fe to Ag is in the range of 1:6 to 1:3.

[0046] According to certain preferred embodiments of the present invention, the pore density of the foamed copper-manganese alloy is in the range of 10-110 PPI.

[0047] According to certain preferred embodiments of the present invention, the compressive strength of the foamed copper-manganese alloy is greater than or equal to 0.5 MPa.

[0048] According to certain preferred embodiments of the present invention, the electrical conductivity of the foamed copper-manganese alloy is greater than or equal to 1.0 × 10⁻⁶. 5 S / m.

[0049] According to certain preferred embodiments of the present invention, the weight gain of the foamed copper-manganese alloy after oxidation in air at 800°C for 100 h is less than or equal to 4.0 wt%.

[0050] According to certain preferred embodiments of the present invention, the pore wall surface of the foamed copper-manganese alloy is further coated with a metal oxide functional layer, wherein the metal oxide functional layer is an array of MnO2 nanosheets or a Co-Mn-O spinel layer.

[0051] Compared with the prior art, the beneficial effects of the present invention are as follows: First, the alloy composition is uniform and controllable: This invention uses pre-alloyed copper-manganese powder as raw material to avoid compositional segregation caused by electrode potential difference during electrodeposition from the source. The thickness deviation of powder deposition is controlled within ±10%, and the composition of the entire pore wall is stable.

[0052] Second, the three-dimensional pore coverage effect is excellent: This invention overcomes the tip effect by using single-gun reciprocating scanning spraying and / or multi-gun spraying, substrate rotation and multiple static placement processes, so that there are no exposed plating or accumulation defects in the deep pores of the foam.

[0053] Third, production is economical and environmentally friendly: the method according to the present invention produces no electroplating waste liquid or high-risk gaseous precursors, and clean production is suitable for industrialization.

[0054] Fourth, it has strong process adaptability: by adjusting the ratio of metal elements in the copper-manganese alloy powder, it can be adapted to different working conditions such as high-temperature fuel cells, water electrolysis, and battery current collectors.

[0055] Fifth, the porosity of the foamed copper-manganese alloy product is adjustable, and the product also has high electrical conductivity, good mechanical properties and good oxidation resistance.

[0056] Sixth, the product can be equipped with various post-processing treatments such as annealing, hydrothermal modification, and precision rolling, realizing multiple uses of one material. Furthermore, the complete set of spraying and sintering equipment is mature, with low investment, high degree of automation, and easy to scale up production in batches. Attached Figure Description

[0057] The accompanying drawings are provided in this specification to more clearly explain the technical solutions of the present invention; however, the art is not limited thereto.

[0058] Figure 1 A process flow diagram of preparing foamed copper-manganese alloy by electrostatic spraying according to the technical solution of the present invention is shown; Figure 2 A scanning electron microscope (SEM) image of the foamed copper-manganese alloy prepared in Example 1 is shown; Figure 3 The X-ray diffraction (XRD) pattern of the foamed copper-manganese alloy prepared in Example 1 is shown; Figure 4 A scanning electron microscope (SEM) image of the foamed copper-manganese alloy prepared in Example 2 is shown. Detailed Implementation

[0059] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments. It will be understood that other embodiments may be implemented without departing from the scope or spirit of the invention. Therefore, the following detailed description is non-limiting.

[0060] Unless otherwise specified, all figures used in this specification to represent characteristic dimensions, quantities, and physical properties should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise stated, the numerical parameters listed in the foregoing specification are approximations, and those skilled in the art can appropriately modify these approximations to obtain the desired properties using the teachings disclosed herein.

[0061] As mentioned above, existing processes for preparing foamed copper-manganese alloys suffer from the following technical challenges: Electrodeposition methods, due to the large potential difference between copper and manganese electrodes, struggle to achieve uniform co-deposition, and are affected by the tip effect, resulting in uneven coating in deep-pore foam and easy exposure of the plating; powder metallurgy methods cannot prepare high-porosity three-dimensional interconnected pore structures, and sintering easily leads to component segregation and blank collapse; slurry coating methods rely on pre-fabricated foamed copper substrates, have long production cycles, and are prone to pore clogging and coating cracking; CVD and PVD equipment are costly and have poor deep-pore coating capabilities. This invention aims to solve one or more of the above technical problems.

[0062] Specifically, the present invention provides a method for preparing foamed copper-manganese alloy by electrostatic spraying. Figure 1 A process flow diagram for preparing foamed copper-manganese alloy by electrostatic spraying according to the technical solution of the present invention is shown, which includes the following steps: (1) Provide a porous substrate and pretreat it, the pretreat including a conductive treatment to make the surface of the porous substrate conductive; (2) Copper-manganese alloy powder is sprayed onto a pretreated porous substrate using electrostatic spraying; (3) Dry and shape the porous substrate that has been electrostatically sprayed; (4) The dried and shaped product is placed in a protective atmosphere for hot degreasing and sintering to obtain a sintered body; (5) Cool the sintered body.

[0063] The following section provides a detailed explanation of each of the above steps and their technical solutions.

[0064] Regarding step (1): Provision and pretreatment of porous matrix This invention uses porous organic foam as a sacrificial template. By spraying copper-manganese alloy powder onto its skeleton and then removing the organic matrix through high-temperature sintering and metallurgically bonding the alloy powder, a three-dimensional interconnected porous alloy skeleton is replicated.

[0065] According to certain preferred embodiments of the present invention, the porous matrix is ​​selected from polyurethane foam, melamine foam, or carbon fiber foam. Polyurethane foam has advantages such as regular pore structure, uniform pore size distribution, low cost, and ease of processing and molding, making it the most commonly used sacrificial template for preparing foamed metals. Melamine foam has better temperature resistance than polyurethane, and its skeleton is finer, making it suitable for preparing foam alloys with high pore density and thin-walled structures. Carbon fiber foam can be partially retained or undergo interfacial reactions with the alloy during high-temperature sintering, making it suitable for preparing carbon-reinforced composite foam materials. According to the technical solution of the present invention, polyurethane foam is preferably used as the matrix.

[0066] According to certain preferred embodiments of the invention, the pore density of the porous matrix is ​​in the range of 10-110 PPI, preferably 30-110 PPI, more preferably 80-110 PPI, and the average pore size is in the range of 100 μm-700 μm. Pore density, i.e., the number of pores per inch, is a parameter characterizing the fineness of the foam pores.

[0067] According to certain preferred embodiments of the present invention, the thickness of the porous matrix is ​​in the range of 1-50 mm, preferably 1-10 mm.

[0068] The pretreatment preferably includes three sub-steps: surface roughening treatment, conductivity treatment, and drying treatment. Its purpose is to improve the surface state of the porous substrate, give it the conductivity required for electrostatic spraying, and improve the bonding and adhesion between the alloy powder and the substrate surface.

[0069] According to some preferred embodiments of the present invention, the pretreatment further includes a surface roughening treatment performed before the conductivity treatment. The surface roughening treatment involves immersing the porous substrate in an alkaline solution with a concentration of 1-5% by weight at 40-60°C for 5-60 minutes. According to some preferred embodiments of the present invention, the alkaline solution is an aqueous sodium hydroxide solution. The original surface of polyurethane foam is relatively smooth and dense, resulting in limited adhesion between it and chemical plating layers or subsequent powder coatings. It is prone to peeling under external force or thermal stress. The alkaline roughening treatment utilizes the hydrolytic etching effect of sodium hydroxide on the ester bonds in the polyurethane molecular chain to form a micron-level rough morphology on the foam skeleton surface, increasing surface energy and mechanical interlocking sites, and improving the adhesion of subsequent plating layers and powders. After the roughening treatment, the foam must be thoroughly rinsed with deionized water to remove residual alkaline solution and avoid contamination of the subsequent chemical plating solution.

[0070] According to certain preferred embodiments of the present invention, the conductivity treatment is performed by electroless nickel plating, electroless copper plating, or coating with conductive carbon paste, thereby reducing the surface resistivity of the porous substrate to 10 Ω·cm. 2 -10 4Ω / sq. The principle of electrostatic spraying is to use a high-voltage electrostatic field to charge powder particles, which then adhere to the grounded workpiece under the action of the electric field force. Organic foam itself is an insulator. If it is not conductive, the powder particles cannot release the charge after reaching the foam surface, which will cause charge accumulation and generate a repulsive effect, resulting in low powder coating rate and uneven coverage. By conductive treatment, a continuous conductive layer is formed on the surface of the foam skeleton, making it a ground electrode in the electrostatic field. After the powder particles arrive, they can quickly release the charge and be stably adsorbed. According to the technical solution of the present invention, the surface resistance is controlled at 10 Ω / sq. 2 -10 4 The requirements for electrostatic spraying can be met within the range of Ω / sq.

[0071] According to certain preferred embodiments of the present invention, the pretreatment further includes a drying process performed after the conductivity treatment, the drying process comprising drying the conductivity-treated porous substrate at 60-80°C for 30-240 minutes.

[0072] Regarding step (2): electrostatic spraying of copper-manganese alloy powder Electrostatic spraying is a crucial step in the preparation of foamed copper-manganese alloys in this invention. It utilizes the Coulomb force of a high-voltage electrostatic field to drive the uniform deposition of pre-alloyed copper-manganese powder into the framework of a three-dimensional porous substrate, achieving omnidirectional coating from the outside in. Compared with traditional electrodeposition and slurry coating, electrostatic spraying offers significant advantages such as controllable composition, strong deep-pore coating capability, and zero waste liquid discharge.

[0073] According to certain preferred embodiments of the present invention, the copper-manganese alloy powder comprises, based on its total weight, 60-90 wt% Cu and 10-40 wt% Mn. The copper-manganese binary alloy is the basic composition system of the present invention. Copper, as the matrix element, provides high electrical conductivity and good plastic processing properties; manganese, as an alloying element, is dissolved in the copper matrix to form a face-centered cubic α-solid solution, which can significantly improve the alloy's strength, hardness, and high-temperature oxidation resistance.

[0074] According to certain preferred embodiments of the present invention, the copper-manganese alloy powder comprises, based on its total weight: 70-85 wt% Cu; 13-28 wt% Mn; and 0.15-2.5 wt% modified metal, wherein the modified metal is composed of Fe and Ag, and the weight ratio of Fe to Ag is in the range of 1:6 to 1:3. According to a preferred embodiment of the present invention, introducing a composite modified metal composed of Fe and Ag into the copper-manganese binary alloy system can achieve synergistic strengthening of the obtained foamed copper-manganese alloy material in terms of conductivity, mechanical properties, and oxidation resistance. Specifically, in terms of conductivity, Ag itself has excellent intrinsic conductivity, and it precipitates in the copper matrix as an Ag-rich phase, constructing a low-resistance electron transport pathway, effectively compensating for the decrease in conductivity caused by lattice scattering due to the solid solution of manganese. Although Fe dissolves in the matrix and causes some electron scattering, by controlling its content to a low level, the conductivity loss can be controlled within an acceptable range. With the synergy of both elements, the foamed copper-manganese alloy material maintains the antioxidant contribution of manganese while significantly improving electrical conductivity compared to the binary system. In terms of mechanical properties, the significant size difference between Fe and Cu atoms leads to substantial lattice distortion when dissolved in the copper-manganese matrix, achieving solid solution strengthening and increasing the yield strength of the pore wall skeleton. Ag promotes atomic diffusion and particle rearrangement during sintering, improving the degree of sintering densification and reducing micropore defects in the pore walls. The synergistic effect of Fe's solid solution strengthening and Ag's sintering-promoting effect significantly improves the compressive strength of the foamed alloy compared to the binary system. Regarding high-temperature oxidation resistance, Fe promotes the diffusion of manganese atoms outwards, accelerating the formation of continuous, dense Mn2O3 and CuMn2O4 spinel-type oxide films, effectively blocking the inward diffusion of oxygen atoms. Ag refines the oxide film grains, reducing microcracks and further enhancing the barrier effect of the oxide film. According to a preferred embodiment of the present invention, the weight ratio of Fe to Ag in the modified metal is in the range of 1:6 to 1:3. When the Ag ratio is below the lower limit (i.e., the weight ratio of Fe to Ag is greater than 1:3), the conductivity enhancement effect is insufficient, and excessive Fe can easily induce the precipitation of brittle intermetallic phases, which impairs mechanical toughness. When the Ag ratio is above the upper limit (i.e., the weight ratio of Fe to Ag is less than 1:6), the solid solution strengthening and antioxidant promotion effects are weakened, and the synergistic advantages of composite modification cannot be fully utilized.

[0075] According to certain preferred embodiments of the present invention, the particle size of the copper-manganese alloy powder is in the range of 5-45 μm, preferably 10-25 μm. The powder prepared by gas atomization in this invention typically exhibits a normal distribution, D 50 (Median particle size) is approximately 10-20 μm, D 90 It is approximately 35-40 μm, and the overall size falls within the 5-45 μm range.

[0076] According to certain preferred embodiments of the present invention, the loose packing density of the copper-manganese alloy powder is 1.5-3.5 g / cm³. 3 .

[0077] According to certain preferred embodiments of the present invention, the copper-manganese alloy powder is a spherical or near-spherical powder prepared by gas atomization. Gas atomization (VIGA, vacuum induction gas atomization) is the mainstream process for preparing high-performance pre-alloyed powders, typically including the following steps: melting the metal raw material into a homogeneous alloy melt in a vacuum induction furnace, flowing into the atomization chamber through a guide tube, being impacted and broken into fine droplets by a high-pressure inert gas flow (usually argon), and the droplets rapidly solidifying into spherical powder during flight.

[0078] According to certain preferred embodiments of the present invention, the process parameters of the electrostatic spraying are as follows: spraying voltage: -40 to -90 kV; distance between the spray gun and the porous substrate: 150-350 mm; powder supply of the copper-manganese alloy powder: 50-200 g / min; rotation speed of the porous substrate: 5-30 rpm.

[0079] According to certain preferred embodiments of the present invention, the electrostatic spraying is performed in 2-6 coats, with the porous substrate left to stand for 2-5 minutes after each coat before the next coat is applied. The reason for using multiple coats instead of a single thick coat is that multiple thin coats combined with a standing process allow the powder in each coat to fully release its charge and achieve stable adsorption. Furthermore, through the Brownian motion and electric field rearrangement effect of the powder particles, they migrate and fill deeper into the pores, significantly improving the deep-pore coating effect.

[0080] According to certain preferred embodiments of the present invention, in the electrostatic spraying, a spraying method is adopted in which a single electrostatic spray gun reciprocates and scans in conjunction with a rotating porous substrate, wherein: the porous substrate rotates at a uniform speed around its own axis, and a single electrostatic spray gun is used to perform reciprocating scanning spraying along the rotation axis of the porous substrate. This method is suitable for spraying elongated or cylindrical foam substrates. The substrate rotation ensures circumferential uniformity, and the reciprocating scanning of the spray gun along the axial direction ensures consistent spraying time at all positions along the axial direction; the combination of these two methods can achieve uniform coverage of the entire substrate surface.

[0081] According to certain preferred embodiments of the present invention, in the electrostatic spraying, a multi-gun coordinated spraying method is adopted in conjunction with a rotating porous substrate, wherein: the porous substrate rotates at a uniform speed around its own axis, and 2-4 electrostatic spray guns are evenly distributed circumferentially around the porous substrate, with the included angle between adjacent spray guns being 120° or 90°. This multi-gun coordinated method is suitable for large-area or batch production scenarios. Three guns evenly distributed at 120° (corresponding to a triangular layout) or four guns distributed at 90° (corresponding to a quadrilateral layout) can simultaneously spray powder onto the substrate from multiple directions, utilizing the electric field superposition effect to enhance deep-hole penetration capability and significantly improve production efficiency.

[0082] According to certain preferred embodiments of the present invention, the electrostatic spraying is carried out in a spray booth with a temperature of 20-35°C and a relative humidity of less than or equal to 60% RH. The spray booth is typically equipped with a constant temperature and humidity system and an exhaust filtration device to maintain stable environmental conditions and recover oversprayed powder, thereby improving material utilization.

[0083] Regarding step (3): drying and shaping According to certain preferred embodiments of the present invention, the drying and shaping includes drying at 80-120°C for 30-120 minutes. The powder after electrostatic spraying is in a loosely packed, physically adsorbed state, making it extremely easy to be knocked off or dispersed by airflow during handling and loading. The purpose of drying and shaping is to create preliminary bonding forces between powder particles and between the powder and the conductive substrate layer, thereby improving the powder layer's resistance to mechanical interference. For pure metal powders, drying itself does not involve a chemical reaction; it mainly removes trace amounts of adsorbed moisture from the powder and utilizes thermal motion to rearrange the particles and make them more compact.

[0084] Regarding step (4): hot degreasing and sintering Hot debinding and sintering are crucial steps determining the final microstructure and properties of foamed copper-manganese alloys. This process is carried out continuously under a protective atmosphere, sequentially completing the thermal removal of the organic matrix, the diffusion bonding between particles, and the densification and strengthening of the framework. According to certain preferred embodiments of the present invention, the hot debinding and sintering comprises a three-stage sintering process consisting of a hot debinding stage, a pre-sintering stage, and a high-temperature sintering stage.

[0085] The first stage is the thermal degreasing stage. According to some preferred embodiments of the invention, the thermal degreasing stage includes: heating to 300-450°C at a heating rate of 1-3°C / min under an inert atmosphere, and holding at that temperature for 30-90 min. According to some preferred embodiments of the invention, the inert atmosphere is nitrogen, argon, or a mixture of nitrogen and argon. According to some preferred embodiments of the invention, the oxygen content in the furnace during the thermal degreasing stage is less than or equal to 100 ppm. The thermal degreasing stage causes the porous organic matrix (such as polyurethane) serving as a sacrificial template to undergo thermal decomposition, transforming into gaseous small molecules and being discharged from the furnace with the protective gas flow, thereby leaving a porous framework green body composed of copper-manganese powder. The purpose of using an inert atmosphere (nitrogen or argon) is to prevent the copper-manganese powder from being oxidized during the heating process.

[0086] The second stage is the pre-sintering stage. According to certain preferred embodiments of the present invention, the pre-sintering stage includes: heating to 700-850°C at a heating rate of 2-5°C / min under a hydrogen / nitrogen mixed atmosphere, and holding at that temperature for 30-60 min. The pre-sintering stage has a dual function: firstly, to reduce the oxide film on the powder surface, and secondly, to achieve preliminary metallurgical bonding between particles.

[0087] Then comes the high-temperature sintering stage. According to some preferred embodiments of the invention, the high-temperature sintering stage includes: heating to 900-1050°C at a heating rate of 3-8°C / min in a hydrogen / nitrogen mixed atmosphere, and holding at that temperature for 60-180 min. According to some preferred embodiments of the invention, the temperature of the high-temperature sintering stage is 950-1020°C. High-temperature sintering is an important stage for the densification of the alloy skeleton and the formation of its properties. At this temperature, the atomic diffusion rate of the copper-manganese alloy is significantly accelerated, the sintering neck continues to grow and thicken, the interfaces between particles gradually disappear, and continuous alloy pore walls are formed. Through volume diffusion and surface diffusion mechanisms, the pores spheroidize and shrink, the degree of skeleton densification is improved, and finally a three-dimensional interconnected foam structure with both certain strength and porosity is obtained.

[0088] According to certain preferred embodiments of the present invention, during the pre-sintering stage and the high-temperature sintering stage, the hydrogen / nitrogen mixed atmosphere is a mixture of hydrogen and nitrogen, wherein hydrogen accounts for 5-25% by volume and nitrogen accounts for 75-95% by volume. According to certain preferred embodiments of the present invention, the dew point of the hydrogen and nitrogen mixture is less than or equal to -40°C. Dew point is an indicator of the dryness of the atmosphere; a lower dew point indicates lower water content.

[0089] According to certain preferred embodiments of the present invention, the hot degreasing and sintering further includes a cooling stage after the high-temperature sintering stage, the cooling stage comprising: cooling down to below 300°C at a cooling rate of ≤ 5°C / min.

[0090] Regarding step (5): cooling of the sintered body Step (5) involves cooling the sintered body to room temperature. The cooling process continues the cooling procedure at the end of the sintering stage, with slow cooling under a protective atmosphere to avoid thermal shock. Once cooled to room temperature, the furnace can be opened and the foamed copper-manganese alloy product can be removed.

[0091] Regarding step (6): Post-processing According to certain preferred embodiments of the present invention, the method further includes a post-processing step (6) after step (5), wherein the post-processing step (6) is selected from one or more of reduction annealing, surface modification, or precision rolling. The post-processing step is used to further optimize the microstructure, surface function, or dimensional accuracy of the product, and to expand the application scenarios of the material.

[0092] According to certain preferred embodiments of the present invention, the reduction annealing includes annealing at 700-900°C for 1-3 hours in a hydrogen atmosphere. The sintered foam alloy may contain internal stresses, and its surface may have trace amounts of oxidation. Reduction annealing in a hydrogen atmosphere can eliminate sintering stresses, homogenize the composition, restore lattice integrity, and further improve the alloy's conductivity and plasticity. Simultaneously, hydrogen can reduce surface oxides that may be generated during cooling, resulting in a bright and clean metal surface.

[0093] According to certain preferred embodiments of the present invention, the surface modification includes growing a metal oxide functional layer on the pore wall surface of the cooled product obtained in step (5) by chemical oxidation, electroplating, or chemical vapor deposition. According to certain preferred embodiments of the present invention, the metal oxide functional layer is a MnO2 nanosheet array or a Co-Mn-O spinel layer. The surface modification aims to endow the foamed copper-manganese alloy with additional functional properties, such as electrocatalytic activity and higher oxidation resistance. MnO2 nanosheet arrays have excellent oxygen evolution reaction (OER) catalytic activity and can be directly used as a self-supporting anode for alkaline water electrolysis after being grown on the surface of foamed copper-manganese, without the need for additional binders and conductive agents, with a short electron transport path and high catalytic efficiency. The Co-Mn-O spinel layer has both conductivity and catalytic activity, and is an ideal functional coating for the surface of solid oxide fuel cell connectors, which can further reduce the surface resistance and suppress high-temperature oxidation. Chemical oxidation methods (such as hydrothermal methods) are simple and low-cost, and are suitable for the growth of nanostructured oxides; electroplating is suitable for preparing dense metal or alloy coatings; chemical vapor deposition can achieve uniform coatings in deep pores.

[0094] According to certain preferred embodiments of the present invention, the precision rolling includes multi-pass rolling, with a reduction of 5-15% per pass. Precision rolling is used to adjust the thickness and porosity of the foam alloy, improving surface smoothness and dimensional accuracy. Using multi-pass rolling with small reductions instead of a single-pass rolling with large reductions is to avoid brittle fracture of the foam skeleton: a 5-15% reduction per pass causes gradual plastic deformation of the pore walls, resulting in a controllable decrease in porosity while maintaining the continuity and integrity of the skeleton. The rolled foam alloy exhibits good thickness uniformity and a smooth surface, making it suitable for applications requiring high dimensional accuracy, such as battery current collectors and electrode substrates.

[0095] According to another aspect of the present invention, a foamed copper-manganese alloy is provided, which is prepared by the method described above.

[0096] According to certain preferred embodiments of the present invention, the foamed copper-manganese alloy has a three-dimensional interconnected pore structure, wherein the porosity is in the range of 60-90%.

[0097] According to certain preferred embodiments of the present invention, the pore walls of the foamed copper-manganese alloy contain 60-90% by weight of Cu and 10-40% by weight of Mn. The pore wall composition is essentially consistent with the composition of the pre-alloyed powder used for spraying, and there is no significant element volatilization or segregation during sintering. This is one of the core advantages of the pre-alloyed powder electrostatic spraying process of the present invention compared with the electrodeposition method: due to the large potential difference between the copper and manganese electrodes in electrodeposition, the actual manganese content of the coating is far lower than the ratio of the plating solution, resulting in serious compositional imbalance; while the present invention ensures uniform composition from the powder source, and the compositional deviation of the entire pore wall of the finished product can be controlled within ±5%.

[0098] According to certain preferred embodiments of the present invention, the pore walls of the foamed copper-manganese alloy comprise: 70-85 wt% Cu, 13-28 wt% Mn, and 0.15-2.5 wt% modified metal, wherein the modified metal is composed of Fe and Ag, wherein the weight ratio of Fe to Ag is in the range of 1:6 to 1:3. As described above, the synergistic modification of Fe and Ag can enhance the comprehensive performance of the copper-manganese alloy in three aspects.

[0099] According to certain preferred embodiments of the present invention, the pore density of the foamed copper-manganese alloy is in the range of 10-110 PPI. The pore density is inherited from the original organic foam template and shrinks slightly after sintering but remains essentially consistent. Products with different pore densities are suitable for different applications: low pore density (10-30 PPI) has large pore size and low flow resistance, suitable for fluid filtration, heat exchange, and other scenarios; high pore density (80-110 PPI) has a large specific surface area, suitable for catalysis, electrode reactions, and other scenarios.

[0100] According to certain preferred embodiments of the present invention, the compressive strength of the foamed copper-manganese alloy is greater than or equal to 0.5 MPa. Compressive strength is an important indicator for measuring the mechanical load-bearing capacity of foamed metals. The foamed copper-manganese alloy of the present invention has a continuous and complete metallurgically bonded structure with no cracks or material defects, and its alloy composition is designed for solid solution strengthening; therefore, its compressive strength can reach above 0.5 MPa, and the optimal Fe-Ag modification scheme can reach above 0.75 MPa. In contrast, foams prepared by traditional slurry coating methods typically have lower compressive strength due to coating cracking and discontinuous bonding.

[0101] According to certain preferred embodiments of the present invention, the electrical conductivity of the foamed copper-manganese alloy is greater than or equal to 1.0 × 10⁻⁶. 5 S / m. Although the conductivity of copper-manganese alloy is lower than that of pure copper due to the solid solution of manganese, it is still much higher than that of most non-metallic conductive materials. The conductivity of the foamed copper-manganese alloy of this invention can reach 10. 6 The S / m level meets the conductivity requirements of current collectors and conductive frameworks in electrochemical devices.

[0102] According to certain preferred embodiments of the present invention, the weight gain of the foamed copper-manganese alloy after oxidation in air at 800°C for 100 h is less than or equal to 4.0% by weight. High-temperature oxidation resistance is a core advantage of copper-manganese alloys compared to pure copper, and is also key to their application in solid oxide fuel cells, high-temperature water electrolysis, and other scenarios. During high-temperature oxidation, manganese preferentially diffuses to the surface, forming a dense Mn-Cu composite oxide film, which prevents further diffusion of oxygen inwards.

[0103] According to certain preferred embodiments of the present invention, the pore wall surface of the foamed copper-manganese alloy is further coated with a metal oxide functional layer, which is an array of MnO2 nanosheets or a Co-Mn-O spinel layer. The surface-functionalized foamed copper-manganese alloy can be used directly as a functional electrode without the need for additional catalytic layer preparation, simplifying the device assembly process. The MnO2 nanosheet array grows vertically on the pore wall surface, exposing a large number of catalytically active sites and bonding firmly to the conductive substrate, exhibiting excellent catalytic activity and stability in the alkaline oxygen evolution reaction.

[0104] This invention, based on electrostatic spraying for preparing copper-manganese foam alloys, offers six advantages: First, the composition is uniform and controllable. Using gas-atomized pre-alloyed powder as raw material, each particle has a consistent composition, avoiding manganese segregation and uneven coating caused by the potential difference between copper and manganese electrodes in electrodeposition, resulting in excellent product consistency. Second, it provides superior three-dimensional pore coverage. Utilizing the electrostatic field's "electric line diffraction" effect for circumferential spraying, substrate rotation, and multiple static rearrangement processes, it overcomes the tip effect, achieving comprehensive and uniform coverage of deep pores without exposed plating or accumulation defects, supporting the preparation of high-pore-density, thick foams. Third, it is economical and environmentally friendly, employing a fully dry process, eliminating electroplating heavy metal waste and high-risk CVD precursors; the equipment is mature and highly automated, suitable for continuous industrial production. Fourth, it offers strong process adaptability. By adjusting the copper-manganese ratio and Fe-Ag modification elements, it can be adapted to SOFC connectors (high manganese for oxidation resistance), battery current collectors (high copper for conductivity), and high-end integrated applications. Fifth, it boasts balanced and outstanding performance, overcoming the shortcomings of pure copper foam's susceptibility to oxidation and pure nickel foam's poor conductivity, achieving a synergistic effect of high conductivity, high strength, and high oxidation resistance. Sixth, it has low barriers to industrialization, as electrostatic spraying and atmosphere sintering are both mature industrial technologies, requiring less equipment investment than CVD / PVD, and is easy to scale up in large quantities.

[0105] The present invention will now be described in more detail with reference to embodiments. It should be noted that these descriptions and embodiments are intended to facilitate understanding of the present invention and are not intended to limit the invention.

[0106] Example In this invention, unless otherwise specified, all reagents used are commercially available products and are used directly without further purification. Furthermore, "%" refers to "weight %" and "parts" refers to "parts by weight".

[0107] Table 1 below lists specific information about the raw materials used in the embodiments and comparative examples of the present invention.

[0108]

[0109] Table 2 below lists specific information about the experimental equipment used in the embodiments and comparative examples of the present invention.

[0110]

[0111] Performance testing methods (I) Conductivity Testing Methods The electrical conductivity of the foamed copper-manganese alloys prepared in the following examples and comparative examples was tested using the DC four-probe method (four-terminal electrode method) as described in the following detailed description. Specific test methods refer to the relevant provisions of GB / T 351-2019 "Methods for Measurement of Resistivity of Metallic Materials". Volumetric conductivity, i.e., the conductivity per unit volume of material, is used for characterization, expressed in S / m.

[0112] The testing instrument used was an ST2258C four-probe resistivity meter, equipped with four linearly arranged probes with a probe spacing of 1 mm. The probes were made of tungsten carbide with a tip curvature radius of approximately 25 μm. Before testing, the foamed copper-manganese alloy sample was cut into square pieces with sides of 50 mm and the original thickness. During testing, the four-probe probes were pressed vertically and gently onto the flat surface of the sample, and a constant DC current (typically 100 mA) was applied to the two outer current probes. The potential difference between the two inner voltage probes was measured. Based on the measured voltage and current values, the sheet resistance Rs of the sample was calculated using Ohm's law. For thin films or sheet-like samples with a thickness much smaller than the probe spacing, a thin-film resistance correction formula was used; for thicker blocky foam samples, a finite thickness correction factor was used for conversion.

[0113] The volume resistivity ρ (unit: Ω•m) is obtained by multiplying the sheet resistance by the sample thickness, i.e.: ρ = Rs × d Where d is the sample thickness (unit: m).

[0114] Conductivity σ (unit: S / m) is the reciprocal of resistivity ρ, i.e., σ = 1 / ρ.

[0115] To ensure the accuracy of the test, five points were measured at different locations for each sample, and the arithmetic mean was taken as the final result.

[0116] (II) Compressive Strength Test Method The mechanical properties of the foamed copper-manganese alloys prepared in the following examples and comparative examples were tested using a quasi-static compression test, as described in the detailed description below. The test method conforms to GB / T 31930-2015 / ISO 13314:2011 "Metallic materials – Ductility test – Compression test of porous and honeycomb metals".

[0117] The testing instrument used was a UTM5305 universal testing machine, equipped with a force sensor with a range of 100 kN and a force measurement accuracy of ±0.5% of the indicated value. The compression fixture used a parallel steel plate indenter with a diameter of 150 mm. During testing, the foamed copper-manganese alloy specimens were machined into cubic specimens with a side length of 25 mm. At least three parallel specimens were prepared for each testing condition, and the results were averaged.

[0118] Before testing, the specimen was placed at the center of the indenter and subjected to quasi-static compression at a constant displacement rate of 0.5 mm / min. The load-displacement curve was continuously recorded until the specimen's compression deformation reached more than 50% of its original height. The test environment temperature was room temperature (23±2℃). The compressive stress was obtained by dividing the load by the initial cross-sectional area of ​​the specimen, and the compressive strain was obtained by dividing the displacement by the initial height of the specimen. The stress-strain curve was then plotted.

[0119] Compressive strength is defined as the first peak stress (i.e., initial collapse stress) on the stress-strain curve, corresponding to the critical stress at which the foam skeleton begins to undergo plastic collapse. For materials whose stress-strain curves do not have a clear initial peak, the compressive stress corresponding to 10% strain is taken as the compressive strength (specified compressive strength).

[0120] In this invention, the compressive strength of the foamed copper-manganese alloy is taken as the initial peak stress, and the unit is MPa.

[0121] (III) High-Temperature Oxidation Weight Gain Test Method The high-temperature oxidation weight gain performance of the foamed copper-manganese alloys prepared in the following examples and comparative examples was tested using the isothermal oxidation weight gain method, as described in detail below. Specific test methods refer to the relevant provisions of GB / T 38430-2019 "Corrosion of Metals and Alloys - Isothermal Exposure Oxidation Test Method for Metallic Materials under High-Temperature Corrosion Conditions". The high-temperature oxidation resistance of the materials was quantitatively evaluated by measuring the weight gain per unit mass after the samples were oxidized at 800°C in still air for 100 h.

[0122] The testing instrument used was an SX2-12-10 box-type high-temperature resistance furnace with a temperature uniformity of ±5℃ and a temperature control accuracy of ±1℃. Before testing, the foamed copper-manganese alloy was cut into sheet-like samples of 20 mm × 20 mm × original thickness, and three parallel samples were prepared for each condition. Before testing, the samples were ultrasonically cleaned with anhydrous ethanol for 5 min to remove surface oil and impurities. After removal, they were dried at 105℃ for 30 min and then cooled to room temperature in a desiccator. The initial mass m0 of each sample was weighed using an analytical balance (accuracy 0.1 mg) and recorded. Then, the samples were placed in a corundum boat. After the furnace temperature reached the set temperature of 800℃ and stabilized, the corundum boat was pushed into the constant temperature zone of the furnace, and timing began. During the oxidation process, the furnace was kept in a natural air atmosphere without forced ventilation. After 100 h of constant temperature oxidation, the corundum boat was removed from the furnace and placed in a desiccator to cool naturally to room temperature. The mass m of each sample was accurately weighed again. t This includes the sample itself and the mass of the oxide scale still attached to the sample.

[0123] Oxidative weight gain (unit: weight %) is calculated using the following formula: Oxidative weight gain (wt%) = [(m t – m0) / m0] × 100% Where m0 is the initial mass of the sample before oxidation, m t This represents the total mass of the sample after oxidation.

[0124] The arithmetic mean of three parallel samples was taken as the final test result.

[0125] In the following preparation examples 1-9, copper-manganese based alloy powders with different compositions were prepared by vacuum induction gas atomization (VIGA).

[0126] Preparation Example 1 (Preparation of Cu-Mn Alloy Powder 1) Weigh out 2100 g of electrolytic copper granules and 900 g of electrolytic manganese flakes, for a total feed of 3000 g, corresponding to a Cu:Mn weight ratio of 70:30. Place the two metal raw materials into the alumina crucible of a vacuum induction gas atomization powder-making furnace. After sealing the furnace, turn on the mechanical pump and diffusion pump to evacuate the furnace until the vacuum level reaches 6.67 × 10⁻⁶. -3 After Pa, high-purity argon gas was introduced into the furnace until the internal pressure reached 0.08 MPa. The induction heating system was started, and the furnace charge was heated to 1350℃ at a heating rate of approximately 15℃ / min, and held for 20 min to allow copper and manganese to fully fuse and form a homogeneous alloy melt. During the holding period, electromagnetic stirring was used to assist in the homogenization of the melt at a stirring frequency of 5 Hz. The alloy melt was then transferred to a boron nitride tundish preheated to 1250℃. The melt was then continuously fed into the atomization chamber through an alumina guide tube with a diameter of 5 mm at a flow rate of approximately 3.5 kg / min. The high-pressure argon atomization system was activated, with the main atomizing gas pressure set to 6.5 MPa, the auxiliary gas pressure to 2.5 MPa, and the gas-liquid ratio to approximately 1.8 Nm. 3 / kg. A high-speed argon gas stream, accelerated by a Laval nozzle, vertically impacts the molten metal stream, breaking it into micron-sized droplets. These droplets then solidify within an 8 m high atomization tower, with a cooling rate of approximately 10⁻⁶. 3 -10 4 K / s. The atomized powder is collected by a primary cyclone separator and then classified by an ultrasonic vibrating screen to extract powder with a particle size range of 10-45 μm as the finished product (i.e., Cu-Mn alloy powder 1).

[0127] The particle size distribution of the obtained Cu-Mn alloy powder 1 was determined using a laser particle size analyzer (Mastersizer 3000). 50 It is approximately 18 μm, D 90 The thickness is approximately 38 μm. The loose bulk density, measured using a loose bulk density meter, is 2.82 g / cm³. 3 The tap density is 3.41 g / cm³. 3 X-ray fluorescence spectroscopy (XRF) analysis showed that the actual composition of the powder was Cu 69.72% by weight and Mn 30.15% by weight.

[0128] Preparation Example 2 (Preparation of Cu-Mn Alloy Powder 2) Weigh out 2550 g of electrolytic copper granules and 450 g of electrolytic manganese flakes, for a total feed weight of 3000 g, corresponding to a Cu:Mn weight ratio of 85:15. Place the two metal raw materials into an alumina crucible in a vacuum induction gas atomization pulverizing furnace. After sealing the furnace, evacuate to a vacuum level of 6.67 × 10⁻⁶. -3 The pressure was increased to 0.08 MPa with high-purity argon as a protective atmosphere. The induction heating system was activated, heating to 1320°C at a rate of approximately 15°C / min, and held for 25 min to ensure complete melting and homogenization of the alloy. During the holding period, electromagnetic stirring at 5 Hz was used to promote compositional homogenization. The melt was transferred to a boron nitride tundish preheated to 1230°C and flowed into the atomization chamber through a 5 mm diameter alumina guide tube at a flow rate of approximately 3.8 kg / min. The atomization parameters were set as follows: main gas pressure 6.0 MPa, auxiliary gas pressure 2.2 MPa, and gas-liquid ratio approximately 1.6 Nm³. 3 / kg. Under the impact of high-pressure argon gas flow, the alloy liquid flow is broken into fine droplets and rapidly solidifies in the atomization tower. After cyclone separation and classification by vibrating screen, powder with a particle size range of 5-40 μm is collected (i.e., Cu-Mn alloy powder 2).

[0129] Upon testing, the D of the obtained Cu-Mn alloy powder 2 was found to be... 50 It is approximately 15 μm in size. The loose bulk density is 3.05 g / cm³. 3 The tap density is 3.68 g / cm³. 3 XRF compositional analysis showed Cu 84.86 wt% and Mn 15.02 wt%.

[0130] Preparation Example 3 (Preparation of Cu-Mn Alloy Powder 3) Weigh out 2400 g of electrolytic copper granules and 600 g of electrolytic manganese flakes, for a total feed of 3000 g, corresponding to a Cu:Mn weight ratio of 80:20. Place the metal raw materials into the alumina crucible of the vacuum induction gas atomization furnace and evacuate to a vacuum level of 6.67 × 10⁻⁶. -3 After Pa, high-purity argon gas was introduced to 0.08 MPa to establish a protective slightly positive pressure atmosphere. The temperature was increased to 1335℃ at a rate of 15℃ / min and held for 22 min to allow copper and manganese to completely fuse and form a homogeneous alloy melt. During the holding period, electromagnetic stirring at 5 Hz was applied to accelerate the diffusion and dissolution of manganese in the copper matrix. The melt was transferred to a boron nitride tundish preheated to 1240℃ and injected into the atomization chamber through a 5 mm diameter alumina guide tube at a flow rate of approximately 3.6 kg / min. The atomization process parameters were: main atomization pressure 6.2 MPa, auxiliary gas pressure 2.3 MPa, and gas-liquid ratio approximately 1.7 Nm. 3 / kg. High-pressure argon gas is accelerated through a tightly coupled annular nozzle and then impacts the liquid metal column vertically at supersonic speed, shearing and breaking it into micron-sized droplets. The droplets undergo rapid solidification during their descent, with a cooling rate of approximately 5 × 10⁻⁶. 3 K / s. After being collected by cyclone, the powder is classified by ultrasonic vibrating screen to remove particles in the 8-42 μm size range, and the resulting powder is the finished product (i.e., Cu-Mn alloy powder 3).

[0131] Testing revealed that Cu-Mn alloy powder 3 has a D... 50 It has a thickness of approximately 12 μm and a loose bulk density of 2.94 g / cm³. 3 The tap density is 3.55 g / cm³. 3 XRF testing showed that the powder composition was Cu 79.81 wt% and Mn 20.08 wt%.

[0132] Preparation Example 4 (Modified Cu-Mn Alloy Powder 1 (Cu 68.5 -Mn 30 -Fe 1.5 Preparation of ) Weigh out 2055 g of electrolytic copper granules, 900 g of electrolytic manganese flakes, and 45 g of pure iron granules, for a total of 3000 g of feed. The corresponding compositions are Cu 68.5% by weight, Mn 30% by weight, and Fe 1.5% by weight. Add the three metal raw materials into the alumina crucible in descending order of melting point. After sealing the furnace, evacuate to 6.67 × 10⁻⁶. -3 The pressure was increased to 0.08 MPa by introducing high-purity argon gas. Induction heating was initiated, and the temperature was increased to 1400℃ at a rate of 15℃ / min, and held for 30 min to allow the three metals to fully fuse. During the holding period, electromagnetic stirring at 8 Hz was applied to enhance melt convection and promote uniform dispersion of iron. The homogenized alloy melt was transferred to a boron nitride tundish preheated to 1300℃ and flowed into the atomization chamber through a 5 mm diameter alumina guide tube at a flow rate of approximately 3.2 kg / min. The atomization parameters were set as follows: main gas pressure 7.0 MPa, auxiliary gas pressure 2.8 MPa, and gas-liquid ratio approximately 2.0 Nm. 3 / kg. The droplets rapidly solidify within the atomizing tower, with a cooling rate of approximately 8 × 10⁻⁶. 3 K / s. After being collected by cyclone, the powder was graded and separated into particles with a diameter range of 10-45 μm to obtain the powder product (i.e., modified Cu-Mn alloy powder 1).

[0133] Testing revealed that the D content of modified Cu-Mn alloy powder 1 was... 10 It is approximately 8.5 μm, D 50 It has a particle size of approximately 19.2 μm and a loose bulk density of 2.78 g / cm³. 3 The tap density is 3.36 g / cm³. 3ICP-OES compositional analysis showed that Cu was 68.37 wt%, Mn was 29.94 wt%, and Fe was 1.56 wt%.

[0134] Preparation Example 5 (Modified Cu-Mn Alloy Powder 2 (Cu 68.5 -Mn 30 -Ag 1.5 Preparation of ) Weigh out 2055 g of electrolytic copper granules, 900 g of electrolytic manganese flakes, and 45 g of pure silver granules, for a total of 3000 g of feed. The corresponding compositions are Cu 68.5 wt%, Mn 30 wt%, and Ag 1.5 wt%. Place the three metal raw materials into an alumina crucible. After sealing the furnace, evacuate to 6.67 × 10⁻⁶. -3 The pressure was increased to 0.08 MPa with high-purity argon as a protective atmosphere. The mixture was heated to 1320℃ at a heating rate of 15℃ / min and held for 25 min to allow the copper, manganese, and silver metals to fully fuse into a homogeneous ternary alloy melt. During the holding period, electromagnetic stirring at 5 Hz was applied to promote compositional homogenization. The melt was then transferred to a boron nitride tundish preheated to 1220℃ and flowed into the atomization chamber through a 5 mm diameter alumina guide tube at a flow rate of approximately 3.5 kg / min. Atomization process parameters: main gas pressure 6.0 MPa, auxiliary gas pressure 2.2 MPa, gas-liquid ratio approximately 1.6 Nm³. 3 / kg. The droplets solidify inside the atomizing tower, with a cooling rate of approximately 6 × 10⁻⁶. 3 K / s. After cyclone separation and vibrating screen classification, the powder product with a particle size range of 10-45 μm is collected (i.e., modified Cu-Mn alloy powder 2).

[0135] Testing revealed that the D of the Cu-Mn-Ag ternary alloy powder... 10 It is approximately 8.0 μm, D 50 It has a particle size of approximately 17.8 μm and a loose bulk density of 2.88 g / cm³. 3 The tap density is 3.48 g / cm³. 3 ICP-OES compositional analysis results were Cu 68.44 wt%, Mn 29.97 wt%, and Ag 1.52 wt%.

[0136] Preparation Example 6 (Modified Cu-Mn Alloy Powder 3 (Cu 82.5 -Mn 16 -Fe 0.3 -Ag 1.2 Preparation of ) Weigh out 2475 g of electrolytic copper granules, 480 g of electrolytic manganese flakes, 9 g of pure iron granules, and 36 g of pure silver granules, for a total of 3000 g of feed. The corresponding composition of this formula is Cu 82.5% by weight, Mn 16% by weight, Fe 0.3% by weight, and Ag 1.2% by weight, with a Fe to Ag weight ratio of 1:4. Load the metal raw materials into an alumina crucible according to their density from highest to lowest. After sealing the furnace, evacuate to a vacuum of 6.67 × 10⁻⁶. -3 The pressure was increased to 0.08 MPa by introducing high-purity argon gas. The temperature was raised to 1340℃ at a rate of 15℃ / min and held for 28 min to allow the four elements to fully fuse and form a homogeneous quaternary alloy melt. Electromagnetic stirring at 8 Hz was applied during the holding period. The melt was transferred to a boron nitride tundish preheated to 1250℃ and flowed into the atomization chamber through a 5 mm diameter alumina guide tube at a flow rate of approximately 3.4 kg / min. The atomization parameters were set as follows: main gas pressure 6.3 MPa, auxiliary gas pressure 2.4 MPa, and gas-liquid ratio approximately 1.7 Nm³. 3 / kg. The droplet cooling rate is approximately 7 × 10⁻⁶. 3 K / s. After being collected by cyclone, the powder is graded and the finished powder product with a particle size range of 10-45 μm is obtained (i.e., modified Cu-Mn alloy powder 3).

[0137] Testing revealed that the modified Cu-Mn alloy powder 3 had a D... 10 It is approximately 7.8 μm, D 50 It has a particle size of approximately 17.2 μm and a loose bulk density of 2.96 g / cm³. 3 The tap density is 3.57 g / cm³. 3 ICP-OES testing showed the composition to be Cu 82.38 wt%, Mn 16.47 wt%, Fe 0.29 wt%, and Ag 1.19 wt%.

[0138] Preparation Example 7 (Modified Cu-Mn Alloy Powder 4 (Cu 75 -Mn 23 -Fe 0.5 -Ag 1.5 Preparation of ) Weigh out 2250 g of electrolytic copper granules, 690 g of electrolytic manganese flakes, 15 g of pure iron granules, and 45 g of pure silver granules, for a total of 3000 g of feed. The corresponding composition of this formula is Cu 75% by weight, Mn 23% by weight, Fe 0.5% by weight, and Ag 1.5% by weight, with a Fe to Ag weight ratio of 1:3. Place the four metal raw materials into an alumina crucible, seal it, and then evacuate it to a vacuum of 6.67 × 10⁻⁶. -3The pressure was increased to 0.08 MPa with high-purity argon gas for protection. The temperature was increased to 1360℃ at a rate of 15℃ / min and held for 30 min to ensure complete melting and homogenization of the alloy. Electromagnetic stirring at 8 Hz was applied during the holding period to enhance mass transfer. The homogeneous melt was transferred to a boron nitride tundish preheated to 1270℃ and injected into the atomization chamber through a 5 mm diameter guide tube at a flow rate of approximately 3.3 kg / min. Atomization process parameters: main gas pressure 6.6 MPa, auxiliary gas pressure 2.6 MPa, gas-liquid ratio approximately 1.85 Nm³. 3 / kg. The droplet cooling rate is approximately 7.5 × 10⁻⁶. 3 K / s. After cyclone separation, the powder is graded to obtain finished powder products with a particle size range of 10-45 μm (i.e., modified Cu-Mn alloy powder 4).

[0139] Testing revealed that the D content of modified Cu-Mn alloy powder 4 was... 10 It is approximately 8.1 μm, D 50 It has a particle size of approximately 18.0 μm and a loose bulk density of 2.85 g / cm³. 3 The tap density is 3.44 g / cm³. 3 ICP-OES composition analysis results were: Cu 74.87 wt%, Mn 22.92 wt%, Fe 0.50 wt%, Ag 1.50 wt%.

[0140] Preparation Example 8 (Modified Cu-Mn Alloy Powder 5 (Cu 70.5 -Mn 28 -Fe 0.25 -Ag 1.25 Preparation of ) Weigh out 2115 g of electrolytic copper granules, 840 g of electrolytic manganese flakes, 7.5 g of pure iron granules, and 37.5 g of pure silver granules, for a total of 3000 g of raw materials. The corresponding composition of this formula is Cu 70.5 wt%, Mn 28 wt%, Fe 0.25 wt%, and Ag 1.25 wt%. Place the four metal raw materials into an alumina crucible, seal the furnace, and evacuate to 6.67 × 10⁻⁶. -3 The pressure was increased to 0.08 MPa by introducing high-purity argon gas. The temperature was raised to 1380℃ at a rate of 15℃ / min and held for 32 min to ensure complete melting and homogenization of the alloy. During the holding period, electromagnetic stirring at 8 Hz was applied to promote the uniform dispersion of trace amounts of Fe and Ag in the high-manganese matrix. The melt was transferred to a boron nitride tundish preheated to 1290℃ and flowed into the atomization chamber through a 5 mm diameter guide tube at a flow rate of approximately 3.1 kg / min. The atomization parameters were set as follows: main gas pressure 6.8 MPa, auxiliary gas pressure 2.7 MPa, and gas-liquid ratio approximately 1.95 Nm. 3 / kg. The droplet cooling rate is approximately 8 × 10⁻⁶. 3K / s. After being collected by cyclone, the powder is graded and the finished powder product with a particle size range of 10-45 μm is obtained (i.e., modified Cu-Mn alloy powder 5).

[0141] Testing revealed that the D content of modified Cu-Mn alloy powder 5 was... 10 It is approximately 8.7 μm, D 50 It has a particle size of approximately 19.6 μm and a loose bulk density of 2.76 g / cm³. 3 The tap density is 3.33 g / cm³. 3 ICP-OES testing showed the composition to be Cu 70.36 wt%, Mn 27.94 wt%, Fe 0.24 wt%, and Ag 1.24 wt%.

[0142] Preparation Example 9 (Preparation of Cu-Mn Alloy Powder 4) Weigh out 2515.5 g of electrolytic copper granules and 484.85 g of electrolytic manganese flakes, for a total feed weight of 3000 g, corresponding to a Cu:Mn weight ratio of 83:16. Place the two metal raw materials into an alumina crucible in a vacuum induction gas atomization pulverizing furnace. After sealing the furnace, evacuate to a vacuum level of 6.65 × 10⁻⁶. -3 The pressure was increased to 0.08 MPa with high-purity argon as a protective atmosphere. The induction heating system was activated, heating to 1320°C at a rate of approximately 15°C / min, and held for 25 min to ensure complete melting and homogenization of the alloy. During the holding period, 5Hz electromagnetic stirring was used to promote compositional homogenization. The melt was transferred to a boron nitride tundish preheated to 1230°C and flowed into the atomization chamber through a 5 mm diameter alumina guide tube at a flow rate of approximately 3.7 kg / min. The atomization parameters were set as follows: main gas pressure 6.0 MPa, auxiliary gas pressure 2.2 MPa, and gas-liquid ratio approximately 1.5 Nm³. 3 / kg. Under the impact of high-pressure argon gas flow, the alloy liquid flow is broken into fine droplets and rapidly solidifies in the atomization tower. After cyclone separation and classification by vibrating screen, powder with a particle size range of 5-40 μm is collected (i.e., Cu-Mn alloy powder 4).

[0143] Upon testing, the D of the obtained Cu-Mn alloy powder 4 was found to be... 50 It is approximately 16 μm in size. The loose bulk density is 3.35 g / cm³. 3 The tap density is 3.47 g / cm³. 3 XRF compositional analysis showed Cu 83.36 wt% and Mn 16.36 wt%.

[0144] Table 3 below lists the component comparisons in Preparation Examples 1-9.

[0145]

[0146] Example 1 In this embodiment, Cu-Mn alloy powder 1 prepared in Preparation Example 1 was used as the matrix of 80 PPI polyurethane foam to prepare foamed copper-manganese alloy by electrostatic spraying-sintering process. The specific steps are as follows: (1) Pretreatment of porous matrix: A pore density of 80 PPI and a density of 25 kg / m³ were used. 3 The polyurethane foam board was cut into samples of 300 mm × 300 mm × 10 mm.

[0147] First, surface roughening treatment is performed: the foam sample is immersed in a 3% by weight NaOH aqueous solution at 50°C for 10 minutes to moderately roughen the polyurethane surface, improving the adhesion of subsequent coatings and powders. After roughening, the sample is removed and repeatedly rinsed with deionized water until neutral.

[0148] Subsequently, a chemical copper plating conductivity treatment was performed: a chemical copper plating working solution was prepared, containing 10 g / L CuSO4•5H2O, 20 g / L sodium potassium tartrate, 10 g / L NaOH, and 10 mL / L formaldehyde. The pH was adjusted to 12.5, and the plating solution temperature was controlled at 60℃. The roughened foam sample was immersed in the plating solution and plated at a constant temperature for 15 min to form a uniform and continuous conductive copper layer on the surface of the foam skeleton. After plating, the sample was removed, rinsed with deionized water, and placed in a hot air circulating oven to dry at 75℃ for 45 min to remove surface adsorbed moisture. A four-probe test showed that the sheet resistance of the conductive foam surface was approximately 500 Ω / sq.

[0149] (2) Electrostatic spraying: Electrostatic powder coating was performed using an OptiStar 4.0 electrostatic powder coating system. Specifically, the pretreated polyurethane foam sample was fixed on a rotatable fixture. Three electrostatic spray guns were evenly distributed around the sample at a 120° circumference, forming a multi-gun coordinated spraying system. Cu-Mn alloy powder 1 prepared in Preparation Example 1 was used as the coating material. The powder was pre-dried under vacuum at 60°C for 2 h to remove adsorbed moisture. The electrostatic spraying process parameters were set as follows: spraying voltage -70 kV (negative polarity), distance between the spray gun and the substrate surface 250 mm, powder feed rate 120 g / min, and substrate rotation speed 15 rpm. The ambient temperature of the spraying chamber was controlled at 25°C, and the relative humidity was controlled below 50% RH. A total of four spraying passes were performed, each lasting 2 min. After each pass, the sample was allowed to stand for 3 min to allow the charged powder to fully rearrange under the electrostatic field and migrate deeper into the pores, ensuring uniform powder deposition even in the deep pore areas of the foam.

[0150] (3) Drying and shaping: Place the sprayed foam sample in a hot air circulating oven and dry it at a constant temperature of 100℃ for 60 minutes.

[0151] (4) Hot degreasing and sintering: The dried sample is placed horizontally in an alumina crucible and sent into a tube-type atmosphere sintering furnace. The following four steps are followed: Thermal degreasing stage: The temperature is increased from room temperature to 400℃ at a rate of 2℃ / min, held for 60 min, and high-purity nitrogen gas (flow rate 5 L / min) is introduced to gradually decompose and vaporize the polyurethane matrix and discharge it out of the furnace with the gas flow.

[0152] Pre-sintering stage: The temperature is increased from 400℃ to 800℃ at a rate of 3℃ / min and held for 45 min. Then, the temperature is switched to H2 / N2 mixed gas (H2 accounts for 10 vol%, dew point ≤ -50℃) to reduce the oxide film on the powder surface under a reducing atmosphere and to induce preliminary diffusion bonding between particles.

[0153] High-temperature sintering stage: The temperature is increased from 800℃ to 1000℃ at a rate of 5℃ / min, held for 120 min, and maintained in a H2 / N2 reducing atmosphere.

[0154] Cooling stage: After the high temperature holding period, the sample is cooled to below 300℃ at a rate of ≤5℃ / min with the furnace, and then naturally cooled to room temperature before being taken out.

[0155] (5) Post-treatment after reduction annealing: The sintered foamed copper-manganese alloy sample was sent back into a tube furnace and annealed at 850°C for 2 h in a pure hydrogen atmosphere (flow rate 3 L / min).

[0156] The final foamed copper-manganese alloy product was found to have a thickness of approximately 9.8 mm and a porosity of approximately 78%. Figure 2 The image shows a scanning electron microscope (SEM) image of the foamed copper-manganese alloy prepared in Example 1. It can be seen that it has a three-dimensional interconnected porous framework structure with continuous and intact pore walls and a dense morphology with interparticle metallurgical bonding on the surface. Figure 3 The X-ray diffraction (XRD) pattern of the foamed copper-manganese alloy prepared in Example 1 is shown. Each diffraction peak corresponds to the characteristic peak of copper-manganese α solid solution, indicating that the product is a face-centered cubic single-phase Cu-Mn solid solution with no obvious impurity phase formation.

[0157] Then, the foamed copper-manganese alloy product was tested according to the test methods for conductivity, compressive strength, and high-temperature oxidation weight gain properties described in detail above. The results showed that the compressive strength was 0.62 MPa and the conductivity was 1.2 × 10⁻⁶ MPa. 6The weight gain after constant-temperature oxidation in air at 800℃ for 100 h is 0.85% by weight (S / m). This foamed copper-manganese alloy product combines high conductivity, good mechanical strength, and good high-temperature oxidation resistance, making it suitable for high-temperature applications such as solid oxide fuel cell (SOFC) stack connectors.

[0158] Example 2-Example 12 Examples 2-12 were carried out in a similar manner to Example 1, except that the type of copper-manganese alloy powder, the type of polyurethane foam, and the electrostatic spraying process parameters were changed as shown in Table 4 below.

[0159] Figure 4 The image shows a scanning electron microscope (SEM) image of the foamed copper-manganese alloy prepared in Example 2, which also has a three-dimensional interconnected porous structure.

[0160] Then, the foamed copper-manganese alloy products prepared in Examples 2-12 were tested according to the test methods for electrical conductivity, compressive strength and high-temperature oxidation weight gain properties described in detail above, and the results are shown in Table 5 below.

[0161] Example 13 In this embodiment, Cu-Mn alloy powder 2 prepared in Preparation Example 2 was used as the matrix, and gradient pore polyurethane foam (one side has a pore density of about 30 PPI (pore diameter of about 550 μm), the other side has a pore density of about 80 PPI (pore diameter of about 180 μm), and the middle is a gradual transition zone) was used as the matrix.

[0162] Specifically, the pretreatment method for the gradient-pore polyurethane foam is the same as in Example 1. The electrostatic spraying process is similar to that in Example 1, except that the electrostatic spraying parameters are adjusted as follows: spraying voltage -60 kV, spray gun distance 200 mm, powder supply 100 g / min, substrate rotation speed 20 rpm, and a total of 5 sprays. Due to the larger pore size on the large-pore side (30 PPI), the powder can more easily enter the interior. By adjusting the spray gun scanning speed, the powder deposition on the large-pore side is slightly higher than that on the small-pore side, forming a gradient thickness coating. The drying, shaping, hot degreasing, and sintering processes are similar to those in Example 1, except that the high-temperature sintering temperature is adjusted to 980℃. After sintering, surface modification is performed, in which a hydrothermal method is used to grow MnO2 nanosheet arrays on the pore wall surface. Specifically, the foam alloy is immersed in a mixed aqueous solution of 0.02 M KMnO4 and 0.05 M Mn(CH3COO)2, and hydrothermally reacted at 120℃ for 6 h. After cooling, it is rinsed with deionized water and then dried at 60℃. The final product has a gradient pore structure, and its surface MnO2 loading was tested to be approximately 2.5 mg / cm³. 2 In 1 M KOH, 10 mA / cm 2The OER overpotential at current density is approximately 280 mV, making it suitable for alkaline water electrolysis hydrogen production anodes.

[0163] Example 14 This embodiment uses Cu-Mn alloy powder 3 prepared in Preparation Example 3 and 110 PPI ultrathin polyurethane foam as the matrix.

[0164] Specifically, the following is selected: 110 PPI polyurethane foam, 2.0 mm thick, with a density of 22 kg / m³. 3 Pretreatment involved electroless nickel plating: the plating solution was an aqueous solution containing 20 g / L NiSO4•6H2O, 25 g / L NaH2PO2•H2O, and 25 mL / L lactic acid, with a pH of 4.5 and a temperature of 85℃, for 20 min. Electrostatic spraying employed a single-gun reciprocating scanning + substrate rotation method, with a substrate rotation speed of 25 rpm, a spraying voltage of -50 kV, a spray gun distance of 180 mm, a powder feed rate of 80 g / min, and three coats. Drying was performed at 90℃ for 45 min. In the sintering process, the temperature was increased to 350℃ at a rate of 1.5℃ / min and held for 45 min (nitrogen gas), increased to 850℃ at a rate of 3℃ / min and held for 30 min (H2 / N2 mixed gas, with H2 accounting for 15% by volume), increased to 1020℃ at a rate of 5℃ / min and held for 90 min, followed by furnace cooling. After sintering, the material undergoes precision rolling using a multi-pass rolling process, with a reduction of 10% per pass, resulting in a final thickness of 0.8 mm and a porosity of approximately 72%. The product exhibits a surface resistivity of less than or equal to 5 mΩ / sq and shows no corrosion or perforation after immersion in 6 M KOH electrolyte for 30 days. It is suitable as a current collector for high-rate batteries such as nickel-zinc and nickel-metal hydride batteries.

[0165] Comparative Example 1 Comparative Example 1 used a conventional electrodeposition method to prepare a foamed copper-manganese alloy, with the same 80 PPI polyurethane foam as in Example 1 as the matrix. The matrix pretreatment was the same as in Example 1, including roughening and electroless copper plating for conductivity. The sample was then placed as the cathode in the electroplating solution. The electroplating solution formulation was: CuSO4•5H2O 40 g / L, MnSO4•H2O 20 g / L, Na2SO4 60 g / L, H3BO3 30 g / L, pH adjusted to 4.0, and the plating solution temperature was 40°C. The electroplating was carried out at 2 A / dm³. 2 Electrodeposition at a current density of 60 min was performed. Due to the standard electrode potential of copper (E... 0 =+0.34 V) is much higher than that of manganese (E) 0=-1.18 V), with a potential difference of 1.52 V, copper ions are preferentially reduced at the cathode, making co-deposition of manganese ions difficult. The actual manganese content in the obtained coating is only about 8% by weight, far lower than the target of 30% by weight. Simultaneously, electroplating exhibits a significant tip effect, with low current density inside the foam channels, resulting in a significantly thinner coating and "white-exposed" areas. After sintering, the product exhibits uneven pore wall composition, with a surface manganese content of approximately 12% by weight and an internal content of only about 3% by weight. Testing revealed that the sample had a compressive strength of 0.35 MPa and an electrical conductivity of 2.2 × 10⁻⁶. 6 Due to its low manganese content, the S / m ratio shows a weight gain of up to 5.8% after oxidation at 800℃ for 100 hours.

[0166] Comparative Example 2 Comparative Example 2 uses a powder slurry impregnation coating method to prepare foamed copper-manganese alloy. Cu-Mn alloy powder 1 from Preparation Example 1 was mixed with PVA binder at a weight ratio of 10:1, and deionized water was added and stirred to prepare a uniform slurry with a solid content of approximately 60% by weight. An 80 PPI polyurethane foam of the same specifications as in Example 1 was impregnated into the slurry. After thorough impregnation, the foam was removed, and excess slurry was squeezed out using a roller press to control the coating amount. The impregnation-squeezing process was repeated three times, followed by drying at 80°C for 2 hours. After drying, debinding and sintering were performed according to the same procedure as in Example 1. Due to the high viscosity of the slurry, it was difficult to penetrate deep into the foam pores, resulting in uneven coating on the inner surface of the pores; and the binder shrinkage during drying caused cracks in the coating. After sintering, cracks and peeling defects were present in the pore walls, and the integrity of the skeleton was poor. Testing showed that the compressive strength of this sample was only 0.28 MPa; the electrical conductivity was 6.5 × 10⁻⁶. 5 S / m; Weight gain after oxidizing at 800℃ for 100h is 3.2% by weight.

[0167] The raw material types and process parameters of Examples 1-14 and Comparative Examples 1-2 are specifically shown in Table 4 below.

[0168]

[0169] Note: Comparative Example 1 is an electrodeposition method and Comparative Example 2 is a slurry coating method. Therefore, there are no electrostatic spraying related parameters, which are indicated by "-" in the table.

[0170] The main performance test results of the foamed copper-manganese alloys prepared in Examples 1-14 and Comparative Examples 1-2 above are shown in Table 5 below.

[0171]

[0172] As can be seen from the test results in Table 5 above, the foamed copper-manganese alloys of Examples 1-14 prepared by electrostatic spraying process of the present invention are superior to the traditional electrodeposition method (Comparative Example 1) and slurry coating method (Comparative Example 2) in terms of the sum of mechanical strength, electrical conductivity and high temperature oxidation resistance.

[0173] Specifically, regarding mechanical compressive strength, the compressive strength of all sample examples was consistently ≥ 0.55 MPa. Example 11, using modified Fe-Ag quaternary alloy powder, achieved a compressive strength of 0.82 MPa, the best performance in this group. However, the mechanical properties of the two comparative process samples showed significant shortcomings. Comparative Example 1, using electrodeposition, had a compressive strength of only 0.35 MPa, while Comparative Example 2, using slurry coating, had a compressive strength as low as 0.28 MPa. This is because traditional electrodeposition is limited by the potential difference between the copper and manganese electrodes, resulting in low manganese content in the pore walls, insufficient alloy solid solution strengthening effect, and uneven coating thickness in the pores, making weak areas prone to plastic collapse. The slurry coating process suffers from poor slurry penetration, coating cracking and detachment after drying and sintering, poor metallurgical bonding continuity of the metal skeleton, and rapid crack propagation under stress, reducing the load-bearing capacity of the foam structure. This invention uses pre-alloyed gas atomized powder combined with electrostatic field full-area coating. The powder particles are uniformly deposited in all parts of the foam skeleton. After sintering, a complete and continuous metallurgical bonding layer is formed on the pore walls. The skeleton is free of cracks and local material shortage defects, and the macroscopic compressive strength is significantly improved.

[0174] Furthermore, regarding high-temperature oxidation resistance, the weight gain rate of all Examples 1-14 after 100 h of air oxidation at 800°C was ≤2.30 wt%, with Examples 10-12, which used Fe and Ag-modified copper-manganese alloy powder, exhibiting a weight gain rate as low as 0.42-0.60 wt%, demonstrating excellent high-temperature oxidation resistance. Comparative Example 1 showed an oxidation weight gain as high as 5.80 wt%, and Comparative Example 2 also reached 3.20 wt%. This is because the manganese content in the electrodeposited samples was lower than the designed ratio, lacking sufficient manganese to form a dense protective oxide film, thus leading to rapid oxidation and weight gain of the copper substrate at high temperatures. Additionally, the pore wall cracks in the samples obtained by slurry coating provided diffusion channels for oxygen, causing oxidation to continue eroding inward from the cracks, thereby exacerbating the oxidation weight gain. This invention precisely controls the Cu and Mn ratio from the powder source, and the compounding of Fe-Ag can further optimize the density of the oxide film, forming a complete and continuous alloy pore wall to isolate oxygen permeation, thereby significantly improving the service life under high temperature conditions and making it suitable for long-term high-temperature service scenarios such as fuel cells and high-temperature water electrolysis.

[0175] Regarding electrical conductivity, the conductivity of all Examples 1-14 is ≥ 1.0 × 10⁻⁶. 6 The S / m ratio meets the conductivity requirements of electrochemical devices. The products from Examples 1-14 of the electrostatic spraying process according to the present invention exhibit no plating delamination or impurity inclusions, achieving a balance between high conductivity and oxidation resistance.

[0176] Obviously, those skilled in the art can make various modifications and variations to this disclosure without departing from the spirit and scope of this disclosure. Therefore, if such modifications and variations fall within the scope of this invention, this disclosure is also intended to include such modifications and variations.

Claims

1. A method for preparing foamed copper-manganese alloy by electrostatic spraying, characterized in that, The method includes the following steps: (1) Provide a porous substrate and pretreat the porous substrate, the pretreat including a conductive treatment to make the surface of the porous substrate conductive; (2) Copper-manganese alloy powder is sprayed onto a pretreated porous substrate using electrostatic spraying; (3) Dry and shape the porous substrate that has been electrostatically sprayed; (4) The dried and shaped product is placed in a protective atmosphere for hot degreasing and sintering, so that the porous matrix is ​​removed and metallurgical bonding is formed between the particles of the copper-manganese alloy powder, thereby obtaining a sintered body; (5) Cool the sintered body.

2. The method according to claim 1, characterized in that, The porous matrix is ​​selected from one of polyurethane foam, melamine foam, or carbon fiber foam; or The thickness of the porous matrix is ​​in the range of 1-50 mm.

3. The method according to claim 1, characterized in that, The conductivity treatment employs electroless nickel plating, electroless copper plating, or coating with conductive carbon paste to reduce the surface resistivity of the porous substrate to 10. 2 -10 4 Ω / sq; The pretreatment further includes a surface roughening treatment performed before the conductivity treatment, the surface roughening treatment comprising immersing the porous substrate in an alkaline solution with a concentration of 1-5% by weight at 40-60°C for 5-60 minutes; or The pretreatment also includes a drying process performed after the conductivity treatment, wherein the drying process includes drying the conductivity-treated porous substrate at 60-80°C for 30-240 minutes.

4. The method according to claim 1, characterized in that, The copper-manganese alloy powder comprises, based on its total weight: 60-90% by weight of Cu; and 10-40% by weight of Mn.

5. The method according to claim 1, characterized in that, The copper-manganese alloy powder comprises, based on its total weight: 70-85% Cu by weight; 13-28% by weight of Mn; and 0.15-2.5% by weight of a modified metal, wherein the modified metal is composed of Fe and Ag, and the weight ratio of Fe to Ag is in the range of 1:6 to 1:

3.

6. The method according to claim 1, characterized in that, The particle size of the copper-manganese alloy powder is in the range of 5-45 μm; The loose packing density of the copper-manganese alloy powder is 1.5-3.5 g / cm³. 3 ;or The copper-manganese alloy powder is a spherical or near-spherical powder prepared by gas atomization.

7. The method according to claim 1, characterized in that, The process parameters for electrostatic spraying are as follows: Spraying voltage: -40 to -90 kV; The distance between the spray gun and the porous substrate is 150-350 mm; The feed rate of the copper-manganese alloy powder is 50-200 g / min; The rotational speed of the porous matrix is ​​5-30 rpm.

8. The method according to claim 1, characterized in that, The hot degreasing and sintering process includes a hot degreasing stage, a pre-sintering stage, and a high-temperature sintering stage, wherein: The thermal degreasing stage includes: heating to 300-450°C at a heating rate of 1-3°C / min under an inert atmosphere, and holding at that temperature for 30-90 min; The pre-sintering stage includes: heating to 700-850℃ at a heating rate of 2-5℃ / min under a hydrogen / nitrogen mixed atmosphere, and holding at that temperature for 30-60 min. The high-temperature sintering stage includes: heating to 900-1050℃ at a heating rate of 3-8℃ / min under a hydrogen / nitrogen mixed atmosphere, and holding at that temperature for 60-180 min.

9. The method according to claim 1, characterized in that, The method further includes a post-processing step (6) after step (5), which is selected from one or more of reduction annealing, surface modification or precision rolling.

10. A foamed copper-manganese alloy, characterized in that, The foamed copper-manganese alloy is prepared by the method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Light foam Mn-Cu alloy high-damping material and preparation method thereof

    CN107460385A

  • Continuous strip-shaped foamy copper-manganese alloy and preparation method thereof

    CN121629210A